A comparative study of fouling-free nanodiamond and nanocarbon electrochemical sensors for sensitive bisphenol A detection. (15th April 2021) - Jiang, Luyun; Santiago, Ibon; Foord, John
Abstract: Bisphenol A (BPA) is a chemical found in polycarbonate plastics and epoxy resins which is biologically harmful and toxicologically relevant at low doses. Electrochemical sensors offer rapid and accurate detection of bisphenols but suffer from electrode fouling. Boron-doped diamond is known for its exceptional capability to resist chemical fouling due to the weak molecular adsorption of s p 3 carbon. In this work, we use nanodiamond to overcome electrode fouling and detect BPA with a low detection limit at 5 nM. Further, we demonstrate the use of nanocarbon-modified electrodes for BPA detection. One-time use nanocarbon electrodes detect BPA through direct oxidation of BPA in a sensitive and reproducible fashion. For continuous monitoring of BPA, we introduce a new approach based on the detection of the by-product of BPA oxidation, hydroquinone (HQ), which acts as a proxy for BPA quantitation without the need of electrode replacement. These findings aim to tackle the challenges of increasing concern of BPA food and water contamination, as an alternative to the more costly and time consuming central laboratory tests. Graphical abstract: Image 1 Highlights: Electrode fouling limits the use of electrochemical Bisphenol A (BPA) sensors but can be minimised using carbon electrodes. We developed a low-fouling, highly sensitive and reliable continuous BPA monitoring system based on boron-doped nanodiamond. Novel nanocarbon-modified electrodes detect BPA as an easy-to-use and low-cost sensor by directly oxidising BPA. We monitor BPA concentration by detecting the BPA oxidation by-product, different from traditional electrochemical sensors.